Analisis Wujud Kebudayaan terhadap Pergeseran Nilai Tradisi Mome’ati Gorontalo dalam Kondisi Postmodern guna Mencegah Hilangnya Makna Esensial Ritual - Dilo, Hanifah Wardatul Jannah (Muttaqien; Indonesian Journal of Multidiciplinary Islamic Studies, 2026)
The Mome’ati tradition is a customary initiation ritual for adolescent Muslim girls in Gorontalo marking the transition to puberty. At the same time, as an institutionally preserved practice, this preservation tends to emphasize ceremonial aspects, thereby risking the loss of its original function as an institution for moral-religious education. This study aims to analyze the extent and mechanisms by which the values ​​and meanings within the Mome’ati tradition have shifted amidst contemporary social conditions. Employing a qualitative method with a literature review design covering the period from 2012 to 2026, the study utilizes qualitative content analysis and hermeneutic-interpretative reading. Koentjaraningrat’s framework of cultural manifestations serves as the primary analytical lens, complemented by three theses regarding postmodern conditions: The Postmodern Condition (Lyotard), The Transformation of Intimacy (Giddens), and Liquid Modernity (Bauman), applied here as conceptual propositions derived deductively from theory rather than as field findings. The study proposes a thesis of internal tradition disintegration: while the artifactual and activity-based forms of Mome’ati remain well-preserved, the system of ideas risks erosion through five mechanisms, namely, the relativization of sacred values, the ceremonialization of custom, intergenerational fragmentation of meaning, cultural commodification, and the weakening of the transmitter’s authority. Practically, the study recommends that the Gorontalo Provincial Government, through the Culture and Tourism Office, mandate value-orientation sessions before the procession and implement tools to evaluate participant understanding during mass Mome’ati events, and that customary institutions develop standardized teaching guidelines for traditional leaders. This thesis remains open to validation through further ethnographic research.